Features of gastritis predisposing to gastric adenoma and early gastric cancer. Issue 10 (1st October 2002) - Meining, A; Riedl, B; Stolte, M
Abstract : Background/Aims: Helicobacter pylori gastritis is a risk factor for the development of gastric cancer. The results of several studies indicate that gastric adenomas, which are considered premalignant lesions, may also be associated with H pylori gastritis. However, it is not clear whether there are different patterns of gastritis in these patients compared with patients with gastric cancer or patients with H pylori gastritis alone. Therefore, this study was designed to investigate the patterns of gastritis in these three groups of patients. Methods: The histological features of gastric mucosa at a distance from the tumour were analysed prospectively in 118 patients with gastric adenoma (mean age, 71.8; female to male ratio, 6 : 4). In addition, for every patient with H pylori associated gastric adenoma an age and sex matched control patient with either H pylori associated early gastric cancer of the intestinal type or H pylori gastritis only was investigated. Results: Only 60 patients (50.9%) with gastric adenoma were infected with H pylori . In the remaining patients, complete atrophic gastritis predominated. In those patients with adenoma and H pylori infection, the gastritis was similar to that seen in patients with early gastric cancer (median score, 2 for activity and degree of gastritis in the antrum and corpus); intestinal metaplasia was common to both groups. These two groups differed significantly from patients with H pylori gastritis only (median grade and activity of gastritis, 1 in antrum and corpus), in whom intestinal metaplasia was rare. Conclusions: It appears that gastric adenomas and gastric intestinal cancer arise by analogous mechanisms. However, owing to severe atrophic gastritis and a lower incidence of H pylori, adenomas do not appear to be definite precursor lesions for gastric cancer.